The anatomy of the Holocaust : selected works from a life of scholarship - Hilberg, Raul 1926-2007 (Vermont studies on Nazi Germany and the Holocaust, 2020)
"Though best known as the author of the landmark 1961 work The Destruction of the European Jews, the historian Raul Hilberg produced a variety of archival research, personal essays, and other works over a career that spanned half a century. The Anatomy of the Holocaust collects some of Hilberg's most essential and groundbreaking writings-many of them published in obscure journals or otherwise inaccessible to nonspecialists-in a single volume. Supplemented with commentary and notes from Hilberg's longtime German editor and his biographer, it not only offers a multifaceted look at the man and the scholar, but also traces the evolution of Holocaust research from a marginal subdiscipline into a diverse and vital intellectual project."--